Faktor Internal dan Ekternal yang Mempengaruhi Underpricing Saham Ketika IPO di DES - Amalia, Lala; Arisnawati, Nur Fani (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2021)
This empirical research was needed to find out the effect of the Earning Per Share,Underwriter Repuation, Inflation, and the exchange rate (Rupiah to US Dollar) onunderpricing of the stock at the time of initial public offering in Syariah Stock List inthe periode time of 2017-2019. The data analysis technique was a multiple linierregression. The result of this reserch showed that simultaneous Earning Per Share,Underwriter Repuation, Inflation, and the exchange rate have a significant effect onstock underpricing. Partially, Earning Per Share has a significant negative effect tounderpricing, Underwriter Reputation doesn’t have a significant negatife effect tounderpricing, Inflation doesn’t have a significant positive effect to underpricing, andThe Exchange Rate has a significant positive effect to underpricing.